H-1 parvovirus-induced oncolysis and tumor microenvironment immune modulation in a novel heterotypic spheroid model of cutaneous T-cell lymphoma - Angelova, Assia L.; Barf, Milena; Just, Alexandra; Leuchs, Barbara; Rommelaere, Jean; Ungerechts, Guy (Cancers, 2024)
The rat protoparvovirus H-1 (H-1PV) is an oncolytic virus known for its anticancer properties in laboratory models of various human tumors, including non-Hodgkin lymphomas (NHL) of B-cell origin. However, H-1PV therapeutic potential against hematological malignancies of T-cell origin remains underexplored. The aim of the present study was to conduct a pilot preclinical investigation of H-1PV-mediated oncolytic effects in cutaneous T-cell lymphoma (CTCL), a type of NHL that is urgently calling for innovative therapies. We demonstrated H-1PV productive infection and induction of oncolysis in both classically grown CTCL suspension cultures and in a novel, in vivo-relevant, heterotypic spheroid model, but not in healthy donor controls, including peripheral blood mononuclear cells (PBMCs). H-1PV-mediated oncolysis of CTCL cells was not prevented by Bcl-2 overexpression and was accompanied by increased extracellular ATP release. In CTCL spheroid co-cultures with PBMCs, increased spheroid infiltration with immune cells was detected upon co-culture treatment with the virus. In conclusion, our preclinical data show that H-1PV may hold significant potential as an ingenious viroimmunotherapeutic drug candidate against CTCL.